Liturgia cristiana e arte Nota in Margine a due Pubblicazioni recenti - Grossi, Vittorino (Augustinianum, 2014)
This note is a presentation and analysis of two recently published volumes by the Libreria Editrice Vaticana: L’Atlante storico della Liturgia, by Keith F. Pecklers, translated from English by Carlo Dezzuto, and Ierotopi cristiani. Alla luce della riforma liturgica del Concilio Vaticano II, by Tiziano Ghirelli. In it, the author higlights the merits and the shortcomings of both publications.